Can you please tell me how to solve this????
![Can you please tell me how to solve this class=](https://us-static.z-dn.net/files/dea/34aeada4282aaa36c2c608362f5d4bcb.png)
Answer:
-2
Step-by-step explanation:
You have to simplify numerator and denominator through factoring. The you should get an expression involving only a + b which is given as -2
Take numerator
[tex]a^2-b^2-12b-36[/tex]
Factor
[tex]-b^2-12b-36[/tex]
[tex]= - (b^2 + 12b + 36)\\\\= -(b+6)^2[/tex]
So numerator becomes
[tex]a^2-\left(b+6\right)^2[/tex]
Apply difference of squares formula: [tex]\displaystyle x^2-y^2=\left(x+y\right)\left(x-y\right)[/tex]
[tex]\mathrm{with\;} x^2 == > a^2, and y^2 == > (b + 6)^2[/tex]
[tex]\implies a^2-\left(b+6\right)^2 \\== \left(a+\left(b+6\right)\right)\left(a-b-6\right)[/tex]
Denominator
[tex]a^2-6a-b^2-6b[/tex]
can be factored as follows
[tex]a^2-b^2 = (a + b) (a -b)[/tex]
[tex]-6a-6b = -6\left(a+b\right)[/tex]
So denominator becomes
[tex]\left(a+b\right)\left(a-b\right)+-6\left(a+b\right)[/tex]
Factor out common term (a+b) to get
[tex]\left(a+b\right)\left(a-b-6\right)[/tex]
So the original expression with Numerator and denominator
[tex]\displaystyle =\frac{\left(a+b+6\right)\left(a-b-6\right)}{\left(a+b\right)\left(a-b-6\right)}[/tex]
Cancel the common factor (a-b-6) to get
[tex]\displaystyle \frac{a+b+6}{a+b}[/tex]
Since a + b = -2, plug in this value of (a+b) in both numerator and denominator to get
[tex]\displaystyle \dfrac{-2 + 6}{-2}[/tex]
[tex]\displaystyle = - 2[/tex]
Answer: -2